Analisis Disiplin Kerja Pegawai pada Sekretariat DPRD Provinsi Banten - Tubagus Bagas Adiya Wijaya Kusuma; Wahyu Widodo; Luis Fiska Rahayu (Badan Penerbit STIEPARI Press, 2025)
This study aims to analyze employee work discipline at the Banten Provincial DPRD Secretariat, focusing on the implementation, policies, and rules that influence employee discipline behavior. Work discipline is an important factor in achieving organizational goals, especially in a government environment that demands high professionalism. The problems identified include late attendance, non-compliance with working hours, lack of responsibility for tasks, and weak supervision, which can have an impact on organizational effectiveness and public service quality. This study uses a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation to obtain a holistic understanding of the situation. The results of the study indicate that the implementation of work discipline at the Banten Provincial DPRD Secretariat still faces various obstacles, both from the internal side of employees and from the institutional side. Factors such as exemplary leadership, reward systems, strict sanctions, and consistent supervision play an important role in improving work discipline. The study further reveals that inconsistencies in applying sanctions and unequal treatment between civil servants and non-civil servants reduce the effectiveness of discipline policies. Therefore, strengthening leadership role models, ensuring fairness, and enhancing transparency in disciplinary enforcement are urgently needed. This study recommends the need for increased assertiveness in implementing regulations, providing motivation, and improving discipline management in order to create a better and more professional work culture, ultimately contributing to improved government performance and accountability.